SASTRA ANAK DI TENGAH DOMINASI MEDIA ELEKTRONIK: Sebuah Kajian Fungsi Sastra Anak sebagai Sarana Pemahaman Kebudayaan dan Kehidupan Untuk Meningkatkan Pendidikan yang Berwawasan Global - Widayati, Mukti (STILISTIKA, 2012)
SASTRA ANAK DI TENGAH DOMINASI MEDIA ELEKTRONIK: Sebuah Kajian Fungsi Sastra Anak sebagai Sarana Pemahaman Kebudayaan dan Kehidupan Untuk Meningkatkan Pendidikan yang Berwawasan GlobalMukti WidayatiPendidikan Bahasa dan Sastra Indonesia FKIP Univet Bangun Nusantara Sukoharjo Jl. Abstract Childrens literature is literature intended for children. Literary elements in it adapted to the needs of extra-aesthetic andaesthetic understanding of the child. As with any work of literaturein general, should childrens literature is loaded with educationalvalues that are useful to humans in living life. By understanding theliterature, the child can be expected to improve the quality ofglobal-minded education. They are not only a broad insight intothe child, even those children who did not become soluble inmodern life that leaves its own culture. Childrens literature is alsocapable of making his readers that the children, being a person ofrefinement and high socio-cultural sensitivity. Electronic means,which offers a variety of entertainment programs memabokkanthe public is not something to be marginalized. Instead it is a challenge for the actors of education and culture to filter and direct the child into a positive development. It just encourages them to compete in developing education in the era of globalization. Key words: childrens literature, educational value, the dominance of electronic media